2012
DOI: 10.1021/om3011195
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Lewis Acidity in Fluoroarylboranes: B(o-HC6F4)3, B(p-HC6F4)3, and B(C6F5)3

Abstract: The Lewis acidic fluoroarylborane B(o-HC6F4)3 (2) was prepared and its Lewis acid strength assessed in comparison to the known, related boranes B(C6F5)3 (1) and B(p-HC6F4)3 (3). Experimental methods based on spectroscopic probes and equilibrium measurements were used to show that B(C6F5)3 is the strongest Lewis acid of the three; while the Lewis acidities of 2 and 3 are comparable, the p-H-substituted isomer is slightly stronger in the tests employed. This contrasts with predictions made on the basis of comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…In this context, we chose Mg(TMP) 2 as base . We expected that since Mg(TMP) 2 has been known as a thermally stable base, its magnesiation strategy for fluoroaryls may open up to the reactions of thermally robust fluoroaryl amido Grignard reagents with a variety of electrophiles …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, we chose Mg(TMP) 2 as base . We expected that since Mg(TMP) 2 has been known as a thermally stable base, its magnesiation strategy for fluoroaryls may open up to the reactions of thermally robust fluoroaryl amido Grignard reagents with a variety of electrophiles …”
Section: Resultsmentioning
confidence: 99%
“…41,42,[47][48][49][50] We expected that since Mg(TMP) 2 has been known as a thermally stable base, its magnesiation strategy for fluoroaryls may open up to the reactions of thermally robust fluoroaryl amido Grignard reagents with a variety of electrophiles. 51,52 At first, we examined the magnesiation of 1 via the treatment of Mg(TMP) 2 in formylation reaction using N,Ndimethylformamide (DMF) as an electrophile (Scheme 1). We found that the magnesiation of 1 readily proceeded at 0°C followed by the reaction with DMF to give the Scheme 1.…”
Section: Syntheses Of 22'-functionalized F 12 Binaphthyl Derivativesmentioning
confidence: 99%
“…The frustration of these FLPs relies on the steric encumbrance of t Bu 3 P and Mes 3 P, in contrast to the fact that B(C 6 F 5 ) 3 ( i ) and the smaller Ph 3 P react to give a regular, inactive Lewis pair Ph 3 PB(C 6 F 5 ) 3 [13] . The high Lewis acidity of B(C 6 F 5 ) 3 stems from the large number of fluorine atoms that decorate the substituents, which give rise to a high charge separation and provide delocalization of the negative charge [14, 15] . Tris(3,4,5‐trifluorophenyl)borane, B(3,4,5‐F 3 C 6 H 2 ) 3 ( ii ) and tris[3,5‐bis(trifluoromethyl)phenyl]borane, B[3,5‐(CF 3 ) 2 C 6 H 3 ] 3 ( iii , „BAr F “) are alternative, less frequently used Lewis acids (Scheme 1), which are slightly less acidic, but possess slightly more accessible boron atoms than BCF ( i ) [16–19] .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the stronger Lewis acidity of fluorophilic electrophiles is essential for the direct heterolytic cleavage of C(sp 3 )-F bonds, given the high activation barrier. The substitution of the fluoride in C(sp 3 )-F bonds to form C-H, C-C, and C-heteroatom bonds has been initiated by neutral, strong aluminum- and boron-based Lewis acids (Stahl et al., 2013, Greb, 2018, Morgan et al., 2013, Koerte et al., 2017, Ahrens et al., 2013, Jaiswal et al., 2017) or cationic species such as [CPh 3 ] + , [SiEt 3 ] + , [ i Bu 2 Al] + , [(C 6 F 5 ) 3 FP] + , and even P(III) dications such as [(bipy)PPh] 2+ bearing weakly coordinating counter anions such as [B(C 6 F 5 ) 4 ] - (Stahl et al., 2013, Klahn et al., 2007, Gu et al., 2009, Forster et al., 2017, Douvris and Ozerov, 2008, Scott et al., 2005, Großekappenberg et al., 2015, Zhu et al., 2016, Chitnis et al., 2018).…”
Section: Introductionmentioning
confidence: 99%